Study on Prezygotic Incompatibility in Some Interspecific Crosses of Vigna - Roy, Mohashweta; Biswas, Animesh; Bhadra, SK (Bangladesh Journal of Genetics and Biotechnology, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Key words: Vigna; Interspecific crosses; Prezygotic incompatibility Bangladesh j. genet. biotechnol. 7(1&2): 15-17 2006 (June & December)